ISSUES OF INDIVIDUAL CAPITALISM IN THE NARRATIVE FILM OF THANK YOU FOR SMOKING AND THE COMPANY MEN - Sukarni Suryaningsih (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2020)
The idea of capitalism always refers to the triumph of the U.S. giant industry. In economic field, American and British capitalism is called as individual capitalism – the contrary of communal capitalism a la Japan and Germany. This paper is intended to examine the identity of economic character of individual capitalism in two Hollywood movies Thank You for Smoking (2006) and The Company Men (2010). Exploring the theory of individual and communal capitalism stated by Lester Thurow, it can be found that through mechanistic relationship, hard individual competition and unending punishment, those all erase emotional bound between individual and corporation. In short it becomes one of the reasons why American industry perishes its superiority slowly.